A study on the factors that influence the switching barriers at TM Point Tanah Merah / Norhayati Hassan - Hassan, Norhayati (2013)
Recently, telecommunication industries face an intense competition and it gives the effects for all telecommunication’s companies. So, the telecommunication companies need to implement the good strategies in order to retain the customer’s loyalty. Switching barriers have a large effect on the customer retention and the researcher interested to study the factors that influence the switching barriers at TM Point Tanah Merah. A set of questionnaires was distributed to the respondents randomly by using fifty (50) respondents to get the data. Several factors that being discussed in this research are switching cost, attractiveness of alternatives and service recovery. The data is analyzed using frequency analysis, reliability, correlation and regression analysis by using Statistical Package for Social Science (SPSS) version 20.0. In this research, the finding shows that switching cost, attractiveness of alternatives and service recovery are significant to the switching barriers. Referring to the finding of this research, it shows that switching cost is the most factors that influence the switching barriers at TM Point Tanah Merah. As a conclusion, three of independent variables such as switching cost, attractiveness of alternatives and service recovery have positive relationship with dependent variable which is switching barriers. So, there are some recommendations from researcher that can help TM Point Tanah Merah to reduce the number of terminations.